(untitled) (Research, Society and Development, 2020)
The present study aims to obtain oat water soluble extract, to determine its centesimal composition and its rheological behavior. The water soluble extract was obtained by immersing the oat flakes in water (70 °C) in a 1:3 ratio (oats/water) for 15 minutes. The extract was characterized by the following parameters: humidity, water activity, total solids, ashes, proteins, lipids, fibers and carbohydrates; For viscosity reading, a Brookfield DVII + Pro viscometer was used using splidlen n°2 with the following rotations: 50, 60, 70, 80, 100, 120, 140 rpm. Through the centesimal composition, it was noticed that the oat extract presented a high water content, low ash values and moderate protein, lipid and fiber values; increased rotational velocity led to an increase in apparent viscosity, which makes flow and heat exchange difficult during thermal processes; oat extract showed behavior of a non Newtonian fluid with Bingham plastic characteristics at the temperature analyzed in this work. Therefore, it is a great alternative as an ingredient for lactose and milk protein free preparations and diets.